2020
DOI: 10.1101/2020.05.07.082172
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pattern recognition receptors confer plant salt tolerance via WRKY18/WRKY40 transcription factors

Abstract: 172/175 words)Pattern recognition receptors (PRRs) bind microbe-and damage-associated molecular patterns (MAMPs/DAMPs, respectively) to enhance host immunity in animals and plants. Here, we report that PRRs also confer salt tolerance in the model plant Arabidopsis thaliana following recognition of cognate ligands, such as bacterial flagellin and EF-Tu and the endogenous Pep peptides. Pattern-triggered salt tolerance (PTST) requires the PRR-associated kinases BAK1 and BIK1, and the NADPH oxidase RBOHD. Transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…The spectrum of effectiveness of the biological control activity seems to be relatively unspecific, as besides the soil-borne fungal diseases mentioned above, WCS417 was demonstrated to control other soil-borne diseases, such as bacterial wilt, caused by Ralstonia solanacearum (Ran et al 2005) and the nematode Xiphinema index (Canchignia et al 2017). In a recent study, colonization of the roots of peppermint (Mentha piperita) by WCS417 improved the antioxidant status of plants grown under drought stress leading to enhanced drought tolerance (Chiappero et al 2019), and in the model plant Arabidopsis (Arabidopsis thaliana) it improved salt tolerance (Loo et al 2020). Hence, WCS417 emerged as a versatile biocontrol agent with capacities that enable it to suppress various soilborne pathogens in a wide range of plant species, and to improve tolerance against abiotic stresses.…”
mentioning
confidence: 99%
“…The spectrum of effectiveness of the biological control activity seems to be relatively unspecific, as besides the soil-borne fungal diseases mentioned above, WCS417 was demonstrated to control other soil-borne diseases, such as bacterial wilt, caused by Ralstonia solanacearum (Ran et al 2005) and the nematode Xiphinema index (Canchignia et al 2017). In a recent study, colonization of the roots of peppermint (Mentha piperita) by WCS417 improved the antioxidant status of plants grown under drought stress leading to enhanced drought tolerance (Chiappero et al 2019), and in the model plant Arabidopsis (Arabidopsis thaliana) it improved salt tolerance (Loo et al 2020). Hence, WCS417 emerged as a versatile biocontrol agent with capacities that enable it to suppress various soilborne pathogens in a wide range of plant species, and to improve tolerance against abiotic stresses.…”
mentioning
confidence: 99%
“…This is one of the most diverse families of transcriptional regulators in plants, and its members are essential components of signaling webs that control a variety of plant activities (Rushton et al, 2010 ); they comprise key plant stress response genes and are involved in multiple immune regulation processes, including both ETI and PTI. WRKY TFs have been reported to promote secondary metabolite synthesis, enhance plant salt tolerance, participate in response to fungus infection (Loo et al, 2020 ), and contribute to bacterial resistance. For example, overexpression of OsWRKYL3 in rice can increase resistance to bacterial blight and rice blast, and it contributes to the disease resistance response mediated by the major resistance factor Xa3/Xa26 (Qiu et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…To investigate whether the lack of FER or HERK1/THE1-4 had an effect on salt-induced gene expression levels, we selected three salt-induced marker genes [17], [40]- [42] and checked their expression in response to salt application.…”
Section: Herk1the1-4 and Fer-4 Mutants Are Affected In Early Responsementioning
confidence: 99%
“…We chose ProPEP3, WRKY40 and RRTF1 because they are strongly induced within 1 h from salt application and because they have been described responsive to a wide number of salt dependent modifications, like cell wall changes, ABAdependent signaling and reactive oxygen species (ROS) [17], [40]- [42] (Table S2). We treated wt, fer-4 and herk1the1-4 seedlings for 1 h and found that the expression level of salt responsive genes was higher in response to salt in the mutant lines when compared to the wt controls ( Figure 1D).…”
Section: Herk1the1-4 and Fer-4 Mutants Are Affected In Early Responsementioning
confidence: 99%
See 1 more Smart Citation